Umar bin Abdul Aziz: A Portrait of a Just Leader and Its Relevance for Today’s Leadership - Rahmi, Aisyah Fadhila; Royyan, Ahmad Arif Hatim Abu; Abdulrahman, Abdulrahman (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study aims to examine the exemplary qualities found in the figure of a caliph from the Umayyad Dynasty, namely Umar bin Abdul Aziz (99–101 AH / 717–720 CE). Umar bin Abdul Aziz is renowned for his justice, simplicity, and commitment to noble Islamic values. The research focuses on his life background, the process of his appointment as caliph of the Umayyad Dynasty, the policies implemented during his reign, and the relevance of his thoughts in the modern era.The method used in this study is library research, drawing from journals, scholarly articles, and relevant books. The findings of this study will highlight Umar’s background as a knowledgeable and wise figure, his appointment as caliph directly by Sulaiman bin Abdul Malik, and his implementation of major reforms, such as eliminating illegitimate taxes, fair redistribution of wealth, and the enforcement of equal justice. His leadership approach is shown to be highly relevant for contemporary leaders, particularly concerning modern issues such as anti-corruption and social justice.